Fournier’s Gangrene in a Neonate: A Case Report - Baghel, B; Dhruv, K (Journal of Nepal Paediatric Society, 2010)
A 15 days newborn presented to paediatric OPD for evaluation of abdominal distension, not accepting feed properly and scrotal swelling. On examination gangrene was found on the scrotum, blood culture showed growth of streptococcal organism. Patient was treated with 3rd generation cephalosporin and local debridement of gangrenous scrotal tissue. Wound got healed by secondary intention and patient was discharged alive and healthy. The outcome of treatment of Fournier’s gangrene in neonate is good. Key words: Fournier’s gangrene; Septicemia; Scrotal swelling; Phimosis; Wound debridement. DOI: 10.3126/jnps.v30i3.3921 J Nep Paedtr Soc 2010;30(3):166-167